2003
DOI: 10.1063/1.1603731
|View full text |Cite
|
Sign up to set email alerts
|

Fractal kinetics in drug release from finite fractal matrices

Abstract: We have re-examined the random release of particles from fractal polymer matrices using Monte Carlo simulations, a problem originally studied by Bunde et al. [J. Chem. Phys. 83, 5909 (1985)]. A certain population of particles diffuses on a fractal structure, and as particles reach the boundaries of the structure they are removed from the system. We find that the number of particles that escape from the matrix as a function of time can be approximated by a Weibull (stretched exponential) function, similar to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0
9

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(101 citation statements)
references
References 14 publications
(22 reference statements)
2
83
0
9
Order By: Relevance
“…The original Kopelman algorithm was given strong theoretical support when it was shown that fractal kinetics owes its emergence to spatial self-organization of the reactants induced by the compact properties of diffusion [102]. Being an extremely significant platform, countless applications of this scheme have been attempted over the years, with a number of these being quite important [103][104][105][106][107]. The interested reader might also benefit from studying the work of Turner et al [103] who carried out an in-depth comparison of various pertinent schemes.…”
Section: Studies In Fractal Kineticsmentioning
confidence: 99%
“…The original Kopelman algorithm was given strong theoretical support when it was shown that fractal kinetics owes its emergence to spatial self-organization of the reactants induced by the compact properties of diffusion [102]. Being an extremely significant platform, countless applications of this scheme have been attempted over the years, with a number of these being quite important [103][104][105][106][107]. The interested reader might also benefit from studying the work of Turner et al [103] who carried out an in-depth comparison of various pertinent schemes.…”
Section: Studies In Fractal Kineticsmentioning
confidence: 99%
“…There are, however, two exceptions. The release from the chitosan-coated particles in acidic medium can be associated with drug diffusion in normal Euclidian space (b = 0.7) [15]. The lowest b value was obtained for the bilayer-coated microspheres in pH = 6.8 (b = 0.42) and according to Kosmidis et al [15] in this case the release can be described by the diffusion mechanism in fractal or disordered substrate.…”
Section: Discussionmentioning
confidence: 98%
“…It indicated that a linear relationship most likely existed between the logarithm of the amount of drug release and time. Kosmidis et al revealed that the Weibull was one of the most appropriate equation to describe the entire duration of the drug release process, thus providing a more generalized picture [48].…”
Section: In Vitro Releasementioning
confidence: 99%